Factor affecting purchasing intention towards green products among Generation Y in Malacca City / Nur Anis Nor Azlan - Nor Azlan, Nur Anis (Faculty of Business and Management, 2018)
The aim of this research is to examine factors affecting generation Y towards intention to purchase green product. In today’s society whereby technology is rapidly growing day by day, it is one of the main causes towards the changes in the environment. Nevertheless, these changes in the environment may be positively or negatively affected. It is the role of people to have the right mind set in order to keep the environment healthy. Thus, this survey is conducted to find out the factors affecting consumers’ attitude in purchasing green products. To zoom in further, this research will be targeted on generation Y, with age ranging from 24 to 40. Therefore, there are four independent variables that had been identified in this research project to understand the factors that could affect generation Y toward intention to purchase green products which are environmental concern, social influences, self-image and man-nature orientation. Primary data was collected for this research proposes. Primary data were collected through questionnaire in order to investigate our research objective. 382 sets of questionnaire were distributed to the respondents. The collected data were then complied by using the Software Package for Social Sciences (SPSS). The SPSS help to carry out the reliability test, descriptive analysis, multiple linear regression and Pearson correlation analysis to test the hypothesis. Consequently, this study carries out to determine the significance of contributing generation Y toward intention to purchase green products in Malacca City.